Pengembangan Media Pembelajaran Sistem Penerangan Sepeda Motor Berbasis Android untuk Meningkatkan Hasil Belajar Siswa Kelas XI di SMK Negeri 3 Kabupaten Tangerang - Raharjo, Naufal Gesang; Iskandar, Ranu; Naryanto, Rizqi Fitri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The use of mobile devices in learning activities is becoming increasingly popular, especially with the presence of Android-based learning media. This study aims to develop Android-based learning media for motorcycle lighting system material, in order to improve the learning outcomes of class XI students at SMK Negeri 3 Tangerang Regency. The development was carried out using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The resulting application was validated by three experts with results ranging from